Lecturers’ Awareness in the use of Edmodo for Teaching - Ayotunde Atanda Falade (Universitas Pendidikan Ganesha, 2023)
The widespread use of e-learning has resulted in higher education institutions around the world experiencing rapid changes as they adapt to the new methods and benefits brought by technology. One of the current trends of LMS is Edmodo. Edmodo is a free web platform that educators can use to create and manage an effective online teaching and learning. This study analyzes university lecturers’ awareness in the use of Edmodo. The study adopted descriptive research of the survey type. The population for this study was made up of all the lecturers in Ekiti- State. Proportional sampling techniques was used to allocate a number of respondents in each school based on their estimated population. The instrument for data collection was an adapted questionnaire. Descriptive and Inferential statistics were used to answer the research question and test the stated hypothesis with the aid of stastistical product and service solution (SPSS) version 20.0 at 0.05 level of significant. The findings indicated that lecturers are aware of the use of Edmodo for teaching. No significant difference exists in the lecturer’s awareness of the use of Edmodo for teaching based on gender. The study concluded that learning can be enhanced and teaching can be effective among lecturers if appropriate technologies are deployed for instruction. Therefore, it was recommended that Lecturers should be encouraged to deploy Edmodo for learning irrespective of their gender.